Cerebellar Kainate Receptor-Mediated Facilitation of Glutamate Release Requires Ca2+-Calmodulin and PKA - Falcón-Moya, Rafael; Losada-Ruiz, Pilar; Sihra, Talvinder S.; Rodríguez-Moreno, Antonio (Frontiers in Molecular Neuroscience, 2018)
We elucidated the mechanisms underlying the kainate receptor (KAR)-mediated facilitatory modulation of synaptic transmission in the cerebellum. In cerebellar slices, KA (3 µM) increased the amplitude of evoked excitatory postsynaptic currents (eEPSCs) at synapses between axon terminals of parallel fibres and Purkinje neurons. KA-mediated facilitation was antagonized by NBQX under condition where AMPA receptors were previously antagonized. Inhibition of protein kinase A (PKA) suppressed the effect of KA on glutamate release, which was also obviated by the prior stimulation of adenylyl cyclase (AC). KAR-mediated facilitation of synaptic transmission was prevented by blocking Ca2+ permeant KARs using philanthotoxin. Furthermore, depletion of intracellular Ca2+ stores by thapsigargin, or inhibition of Ca2+-induced Ca2+-release by ryanodine, abrogated the synaptic facilitation by KA. Thus the KA-mediated modulation was conditional on extracellular Ca2+ entry through Ca2+-permeable KARs as well as and mobilisation of Ca2+ from intracellular stores. Finally, KAR-mediated facilitation was sensitivity to calmodulin inhibitors, W-7 and calmidazolium, indicating that the increased cytosolic [Ca2+] sustaining KAR-mediated facilitation of synaptic transmission operates through a downstream Ca2+/calmodulin coupling. We conclude that, at cerebellar parallel fibre-Purkinje cell synapses, presynaptic KARs mediate glutamate release facilitation and thereby enhance synaptic transmission through Ca2+-calmodulin dependent activation of adenylyl cyclase/cAMP/protein kinase A signalling.